The complete chloroplast genome sequence of the CAM epiphyte Spanish moss (Tillandsia usneoides, Bromeliaceae) and its comparative analysis - Poczai, Péter (PLoS One, 2017)
Spanish moss (Tillandsia usneoides) is an epiphytic bromeliad widely distributed throughout tropical and warm temperate America. This plant is highly adapted to extreme environmental conditions. Striking features of this species include specialized trichomes (scales) covering the surface of its shoots aiding the absorption of water and nutrients directly from the atmosphere and a specific photosynthesis using crassulacean acid metabolism (CAM). Here we report the plastid genome of Spanish moss and present the comparison of genome organization and sequence evolution within Poales. The plastome of Spanish moss has a quadripartite structure consisting of a large single copy (LSC, 87,439 bp), two inverted regions (IRa and IRb, 26,803 bp) and short single copy (SSC, 18,612 bp) region. The plastid genome had 37.2% GC content and 134 genes with 88 being unique protein-coding genes and 20 of these are duplicated in the IR, similar to other reported bromeliads. Our study shows that early diverging lineages of Poales do not have high substitution rates as compared to grasses, and plastid genomes of bromeliads show structural features considered to be ancestral in graminids. These include the loss of the introns in the clpP and rpoC1 genes and the complete loss or partial degradation of accD and ycf genes in the Graminid clade. Further structural rearrangements appeared in the graminids lacking in Spanish moss, which include a 28-kb inversion between the trnG-UCC–rps14 region and 6-kb in the trnG-UCC–psbD, followed by a third <1kb inversion in the trnT sequence.